2010
DOI: 10.1055/s-0029-1245526
|View full text |Cite
|
Sign up to set email alerts
|

Sonoelastography in the Diagnosis of Malignant and Benign Breast Lesions: Initial Clinical Experiences

Abstract: Zusammenfassung ! Ziel: Ziel der prospektiven Untersuchung war es, Ultraschall-Elastografie, B-Bild-Sonografie und Mammografie hinsichtlich ihrer Aussagekraft zur Dignität von Herdbefunden zu vergleichen. Weiterhin wurde untersucht, ob sich die Ergebnisse in der Gruppe palpabler Befunde von denen in der Gruppe nicht palpabler Befunde unterscheiden. Material und Methoden: Es wurden 97 histologisch ungesicherte Herdbefunde (66 benigne, 31 maligne) untersucht. Sensitivität, Spezifität, positiv (PPW) und negativ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…Malignant lesions have a harder structure than benign lesions, and therefore are less elastic due to increased fibrosis and desmoplastic reaction in their structure. When used in conjunction with B-mode US, the latter's sensitivity was increased [7]. AME often has a benign clinical course; however, malignant transformation can rarely develop from one or both cellular components [8].…”
Section: Discussionmentioning
confidence: 99%
“…Malignant lesions have a harder structure than benign lesions, and therefore are less elastic due to increased fibrosis and desmoplastic reaction in their structure. When used in conjunction with B-mode US, the latter's sensitivity was increased [7]. AME often has a benign clinical course; however, malignant transformation can rarely develop from one or both cellular components [8].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, researches have been performed on the use of the elastography technique on discrimination of malignant and benign bulks [14][15][16]. But no study searching the existence of predictive power of prognosis and relation with tumoral prognostic factors of this technique is found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Using scores 1-3 for benign and scores 4 and 5 for malignant lesions, elasticity showed a sensitivity of 87% and a specificity of 90%. In the publication of Hatzung et al [30], the same score system was applied, but they found the highest sensitivity for elastography using scores 1 and 2 for benign and scores 3-5 for malignant lesions. The sensitivity was 71%, the specificity 48%, the ppv 39%, and the npv 78%.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the publications, elasticity is not studied as a stand-alone feature. It is used as a complementary technology to B-mode imaging [22,30]. Based on the literature, the sensitivity of B-mode breast US varies from 57% to 97% and the specificity from 60% to 90%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation